Pola Pelembagaan Pencegahan dan Penanganan Kekerasan Seksual di Perguruan Tinggi - Hidayati, Emi; Fatimah, Nurul; Muftiyah, Al (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The study discusses the dynamics of the implementation of the policy of the Prime Minister No. 30 of 2021 on the prevention and handling of sexual violence at the College of Waterwangi district and discovered institutional patterns of prevention and handling of sexual violence at the College.The research method used is qualitatively descriptive.Data collection techniques using primary and secondary data.Technical data analysis using: 1) data codification; 2) classification; 3) drawing of conclusions.To verify the validity of data using data triangulation.The correspondence of the results of this research is: 1) the involvement of the college with the regional government in the Waterwangi district before the release of the policy number 30 of 2021 permendikbud has shown significant collaboration.Programmes related to violence against women and children have been carried out through special participation forums at district level. College is actively involved in action. 2 ) local government, although involved in previous cooperation, are limited in the authority to intervene in the implementation of this new policy.3 ) major challenges in the implementation of policy ppks in college is the limited human resources and financial.4 ) blended institution was the idea of new legal status was based on obstacles and challenge in the research offers the interaction in vertical kelembagan hierarchy which is not only with the level of policy, but requires consolidated with authority pemiliki knowledge and supervision.